Electrolyte-supported solid oxide fuel cell and preparation method thereof
The electrolyte and electrode layers are prepared by casting film formation and screen printing technology, and through isostatic pressure treatment and specific sintering processes, the problem of electrolyte-supported solid oxide fuel cells being easily broken and poorly bonded with the electrode layers during testing or stacking is solved, achieving the high structural strength and stable electrochemical performance of the battery.
Patent Information
- Application Number
- CN202411843959.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-03-21
AI Technical Summary
The existing electrolyte-supported solid oxide fuel cells are prone to breaking during testing or stacking, and the bonding effect between the electrode layer and the electrolyte layer is poor, resulting in unstable battery performance.
Cast film formation and screen printing technology are used to prepare electrolyte green body and electrode layer. The roughness of the surface of electrolyte green body is increased by isostatic pressure treatment, the bonding force between the electrode layer and the electrolyte layer is improved, and the structural tightness and strength of the battery are improved through a specific sintering process.
The close combination of the electrode layer and the electrolyte layer is achieved, the structural strength and electrochemical performance of the battery are improved, the production cost is reduced, and the problem of the battery being easily broken during testing or stacking is solved.
Smart Images

Figure CN119674102A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to an electrolyte-supported solid oxide fuel cell and a preparation method thereof. Background Art
[0002] SOFC (Solid Oxide Fuel Cell) is a highly efficient energy conversion device that uses the electrochemical reaction between hydrogen or combustible gas (such as natural gas, methane, etc.) and oxygen to directly convert chemical energy into electrical energy and thermal energy. In this process, the fuel undergoes oxidation reaction at the anode, oxygen undergoes reduction reaction at the cathode, and electrons flow through the external circuit to generate electrical energy.
[0003] According to the support, solid oxide fuel cells can be divided into three types, namely anode-supported, electrolyte-supported and cathode-supported. Electrolyte-supported fuel cells are power generation devices that directly convert chemical energy into electrical energy. The core of the fuel cell is the electrolyte material, which determines the performance and stability of the fuel cell. This type of fuel cell introduces hydrogen and oxygen between the positive and negative electrodes. Under the action of the electrolyte, the hydrogen molecules lose electrons at the positive electrode and combine with oxygen at the negative electrode to form water, thereby releasing electrical energy. In this process, the conduction of ions in the electrolyte material is the key to generating electrical energy.
[0004] Compared with anode and cathode supports, electrolyte supports have obvious advantages in mechanical strength, thermal stability and long-term stability. At present, the materials used as electrolytes on the market are mostly zirconium oxide, cerium oxide, etc., and are doped with rare earth elements. Among them, SSZ (Sc-doped zirconium oxide substrate) has higher conductivity and long-term stability, which can reduce the operating temperature of SOFC, reduce energy consumption, and improve energy conversion efficiency. It is widely used in fuel cell electrolyte materials. For example, patent CN 102180669 A discloses a method for co-sintering anode and cathode of an electrolyte-supported solid oxide fuel cell. This method places a solid electrolyte substrate with cathode and anode slurries in a sintering furnace, and co-sinters the cathode and cathode through a step-by-step sintering process, thereby simplifying the existing sintering process and shortening the existing sintering time. The electrolyte substrate used is a YSZ (yttria-stabilized zirconia) substrate or a SSZ substrate. In order to solve the problem of easy breakage during testing or stacking, CeO2 accounting for 0.1% to 5% of the anode raw material is added to the anode to adjust the high-temperature shrinkage rate and thermal expansion coefficient of the anode to match the cathode. However, it does not disclose the preparation method of the electrolyte substrate and how to improve the bonding effect between the electrolyte substrate and the electrode layer. Therefore, it is of great innovative significance to provide a solid oxide fuel cell with a compact structure, excellent structural strength, and strong bonding with the electrode layer. Summary of the invention
[0005] Based on the above prior art, the primary purpose of the present invention is to provide a method for preparing an electrolyte-supported solid oxide fuel cell.
[0006] Another object of the present invention is to provide an electrolyte-supported solid oxide fuel cell prepared by the above method.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing an electrolyte-supported solid oxide fuel cell comprises the following steps:
[0009] (1) mixing the oxide ceramic powder with an organic solvent, a dispersant, a plasticizer, and a binder, dispersing the mixture by ball milling, removing bubbles in vacuum, filtering the mixture, and then forming a film by tape casting to obtain an electrolyte green body;
[0010] (2) isostatically pressing the electrolyte green body obtained in step (1), drying it, stacking it, debinding and sintering it, washing it, and drying it to obtain an electrolyte sheet;
[0011] (3) printing the cathode slurry and the anode slurry on both sides of the electrolyte sheet obtained in step (2) by screen printing, and drying to obtain a single-chip single cell;
[0012] (4) The single cell obtained in step (3) is sandwiched with an electrolyte sheet, and then debinding and sintering are performed to obtain an electrolyte-supported solid oxide fuel cell.
[0013] Furthermore, the oxide ceramic powder in step (1) is YSZ or SSZ ceramic powder with a particle size of 0.1 to 1.5 μm.
[0014] Furthermore, the organic solvent in step (1) is one or more of toluene, ethanol, isopropanol, and acetone; and the amount of the organic solvent is 30% to 70% of the mass of the oxide ceramic powder.
[0015] Furthermore, the dispersant in step (1) is PVA (polyvinyl alcohol) or PAA (polyacrylic acid); the amount of the dispersant is 0.5% to 3% of the mass of the oxide ceramic powder.
[0016] Furthermore, the plasticizer in step (1) is at least one of PEG (polyethylene glycol), DOP (dioctyl phthalate), and DBP (dibutyl phthalate); and the added amount of the plasticizer is 5% to 10% of the mass of the oxide ceramic powder.
[0017] Furthermore, the binder in step (1) is at least one of MC (polymethyl methacrylate) and PVB (polyvinyl butyral); the added amount of the binder is 5% to 15% of the mass of the oxide ceramic powder.
[0018] Furthermore, the filtration in step (1) refers to filtration using a fiber filter element or a stainless steel filter screen with a mesh size of 100 to 500.
[0019] Furthermore, the thickness of the film formed by the casting in step (1) is controlled between 120 and 200 μm, and the temperature is between 30 and 80°C.
[0020] Furthermore, in the isostatic pressing process in step (2), rough materials (such as paper or other rough materials) are coated on both sides of the electrolyte green body to create certain rough textures (such as concave and convex grooves) on the surface of the green body, and the roughness is controlled between 1 and 3 μm.
[0021] The present invention can increase the three-phase interface reaction area and improve the reaction efficiency by roughening the surface of the green body, and at the same time greatly enhance the adhesion of the electrode layer and the electrolyte layer. The rough texture can be determined by a roughness detector, and the roughness is controlled to be about 1 to 3 μm to prevent excessive roughness from causing strength reduction.
[0022] Furthermore, the isostatic pressing treatment in step (2) is performed under a pressure of 30 to 150 MPa, a temperature of 30 to 85° C., and a time of 20 to 150 min.
[0023] Furthermore, the drying in step (2) refers to low-temperature drying at a temperature of 40 to 70° C. for 2 to 5 hours.
[0024] The present invention can dry the residual solvent of the blank through low-temperature drying, which is more conducive to subsequent binder removal, and at the same time can increase the hardness of the blank, reduce deformation damage caused by manual operation in subsequent processes, and facilitate transportation.
[0025] Furthermore, the number of stacked layers in step (2) is 3 to 10, and the stacked electrolyte green bodies are pressed up and down with alumina porous plates having a weight of less than 200 g and a porosity of 20% to 40%.
[0026] Furthermore, in the debinding sintering in step (2), the debinding section has a heating rate of 0.5-2°C / min, a temperature of 250-550°C, and is kept warm for 2-5 hours; the sintering section has a heating rate of 1-3°C / min, a temperature of 1250-1480°C, and is kept warm for 3-6 hours; and then the temperature is reduced to 800°C at a cooling rate of 1-3°C / min, and then naturally cooled to room temperature.
[0027] Furthermore, the cathode slurry in step (3) includes a cathode current collecting layer powder slurry and a cathode active layer powder slurry; the cathode current collecting layer powder slurry is LSM (lanthanum strontium manganese powder), LSC (lanthanum strontium cobalt powder) or LSCF (lanthanum strontium cobalt iron powder) powder slurry with a powder particle size of 0.2 to 1.5 μm; the cathode active layer powder slurry is a mixed slurry of cathode current collecting layer powder and electrolyte oxide ceramic powder in a mass ratio of 1:1 to 1:3; the anode slurry includes an anode current collecting layer powder slurry and an anode active layer powder slurry; the anode current collecting layer powder slurry is NiO powder slurry with a powder particle size of 0.2 to 1.5 μm; the anode active layer powder slurry is a mixed slurry of anode current collecting layer powder and electrolyte oxide ceramic powder in a mass ratio of 1:1 to 1:3.
[0028] Further preferably, the screen printing makes the thickness of the cathode current collecting layer 5-40 μm, the thickness of the cathode active layer 5-20 μm, the thickness of the anode current collecting layer and the anode active layer 5-30 μm; and the drying temperature is 90-130°C.
[0029] Furthermore, in the debinding sintering in step (4), the debinding section has a heating rate of 0.2-1.5°C / min, a temperature of 200-500°C, and is kept warm for 1-4 hours; the sintering section has a heating rate of 0.5-2°C / min, a temperature of 1050-1300°C, and is kept warm for 2-5 hours; and then the temperature is reduced to 600°C at a cooling rate of 1-3°C / min, and then naturally cooled to room temperature.
[0030] An electrolyte-supported solid oxide fuel cell is prepared by the above method.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The preparation method of the present invention uses molding methods such as casting and printing, which can achieve large-scale mass production and effectively reduce costs; and through a specific preparation process, it solves the problems that often occur in the preparation process of single batteries, such as loose bonding of electrode layers, resulting in falling off, excessive contact resistance, excessive battery warping, and easy breakage. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 and Figure 2 The cross-sectional SEM image and the planar SEM image of the electrolyte sheet obtained in Example 1 are respectively;
[0034] Figure 3 and Figure 4 The cathode cross-section SEM image and anode cross-section SEM image of the monolithic single cell obtained in Example 1 are respectively. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0036] Example 1
[0037] A method for preparing an electrolyte-supported solid oxide fuel cell comprises the following steps:
[0038] (1) Prepare a certain amount of SSZ powder with a D50 of 0.5 μm, add an organic solvent (a mixed solvent of toluene, ethanol, and isopropanol in a volume ratio of 1:1:1) into a ball mill, and the amount of organic solvent added is 40% of the mass of the SSZ powder. Then, add 1% of the mass of the SSZ powder as a PVA dispersant and stir to dissolve. Then, add the prepared SSZ powder and ball mill it on a ball mill for 30 minutes. Then, add 7% of the mass of the SSZ powder as DBP and 10% of the PVB and ball mill it for 6 hours. Transfer the material to a sand mill and continue to disperse it for 30 minutes. After filtering, transfer it to a degassing tank. Defoaming treatment was carried out under negative pressure of -100 KPa, and stirring was continued. After 30 minutes, a 200-mesh stainless steel filter was installed and connected to the feeding port of the casting machine. The viscosity of the slurry was measured to be 1000 mPa.s after sampling. The maximum temperature of the drying tunnel was adjusted to 70°C, and the knife height was controlled to control the casting thickness to 180 μm. The casting was completed and divided into green rolls to obtain the electrolyte green rolls.
[0039] (2) The electrolyte green sheet obtained in step (1) is punched into a 100*100 mm square, and the green sheet is sandwiched with a paper with a roughness of 3 μm, and subjected to a nylon film vacuum heat sealing treatment, and then placed in an isostatic press, and maintained at 60°C and 80 MPa for 40 min. After the pressure maintenance is completed, it is cooled to room temperature, taken out and unpacked, and baked at 50°C for 30 min. The treated electrolyte green sheet is stacked in 5 layers, placed on an alumina porous plate with a porosity of 30% (the weight is less than 200 g, otherwise it will affect the shrinkage of the product and cause cracking), and then covered with a plate of the same type, and the temperature is increased to 450°C at a rate of 0.5°C / min, and maintained for 3 h, and then the temperature is increased to 1400°C at a rate of 1°C / min, and maintained for 3 h, and then the temperature is decreased to 800°C at a rate of 2°C, and naturally cooled to room temperature, sintering is completed, and cleaning and drying are performed to obtain an electrolyte sheet. The roughness of the two sides of the electrolyte sheet was measured to be 2.1μm and 2.2μm respectively, and the thickness was 140μm.
[0040] (3) The cathode and anode powders are selected as LSM and NiO, respectively, with D50 = 0.8 μm. For the cathode active layer, the LSM-SSZ powder is mixed evenly in a ratio of 1:1, pine alcohol and ethyl cellulose are added, and the mixture is dispersed by ball milling with a planetary ball mill. After dispersion, a three-roll mill is used for multiple rolls. The fineness of the slurry is detected by a fineness scraper and is about 3 μm. The slurry configuration is completed and printed by a screen printer. Similarly, the cathode current collector layer is completed: the LSM layer is printed. For the anode active layer, the NiO-SSZ powder is mixed evenly in a ratio of 1:1, and the printing is completed as above. The anode current collector layer is a NiO layer, and the principle is the same as above. It should be noted that after each single layer is printed, it is dried and the thickness is measured before printing the next layer. After printing, it is dried at 110°C to obtain a single cell.
[0041] (4) Place the monolithic cell obtained in step (3) on the electrolyte sheet, and then cover it with the electrolyte sheet for clamping. The electrolyte sheet can be reused. Heat it to 400°C at a rate of 0.5°C / min in a debinding and sintering furnace, keep it warm for 2 hours, then heat it to 1200°C at a rate of 1°C / min, keep it warm for 3 hours, and then cool it to 600°C at a rate of 2°C / min. End the program and cool it naturally to room temperature to obtain an electrolyte-supported solid oxide fuel cell.
[0042] The cross-sectional SEM image and planar SEM image of the electrolyte sheet obtained in this example are shown in FIG. Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the electrolyte fragment has a compact cross-sectional structure with very few pores, which can provide excellent structural strength. Figure 2 It can be seen that the surface of the electrolyte sheet has a concave-convex structure. The rough texture created can increase the bonding force with the electrode layer and increase the three-phase interface reaction area.
[0043] The cathode cross-section SEM images and anode cross-section SEM images of the monolithic single cell obtained in this embodiment are shown in FIG. Figure 3 and Figure 4 As shown. Figure 3 It can be seen that the thickness of the cathode active layer and the current collecting layer is about 10 μm, the cathode presents a loose porous structure, and is closely connected to the electrolyte cross section without microcracks or holes. Figure 4 It can be seen that the thickness of the anode active layer and the current collecting layer is about 5μm, and they also present a loose porous structure. They are tightly connected to the electrolyte cross section without any microcracks or holes.
[0044] The electrochemical performance results of the electrolyte sheet obtained in this example, the performance test of the single-sheet single cell and the obtained fuel cell tested at 850° C. are shown in Table 1 below.
[0045] Table 1
[0046] Electrolyte sheet relative density Electrolyte sheet warping Single cell warping Fuel Cell OCV Fuel cell power density 98.4% 160μm 200μm 1.25V <![CDATA[400mW / cm 2 ]]>
[0047] Example 2
[0048] A method for preparing an electrolyte-supported solid oxide fuel cell comprises the following steps:
[0049] (1) Prepare a certain amount of YSZ powder with a D50 of 1.0 μm, add an organic solvent (a mixed solvent of toluene, ethanol, and isopropanol in a volume ratio of 1:1:1) into a ball mill, and the amount of organic solvent added is 50% of the mass of the YSZ powder. Then, add 0.5% of the mass of the YSZ powder as PAA dispersant and stir to dissolve. Then add the prepared YSZ powder and ball mill it on a ball mill for 30 minutes. Then, add 5% of the mass of the YSZ powder as DOP and 5% of the mass of the YSZ powder and ball mill it for 6 hours. Transfer the material to a sand mill and continue to disperse it for 30 minutes. After filtering, transfer it to a degassing tank. Defoaming treatment was carried out under negative pressure of -100 KPa, and stirring was continued. After 30 minutes, a 200-mesh stainless steel filter was installed and connected to the feeding port of the casting machine. The viscosity of the slurry was measured to be 860 mPa.s after sampling. The maximum temperature of the drying tunnel was adjusted to 70°C, and the knife height was controlled to control the casting thickness to 180 μm. The casting was completed and divided into green rolls to obtain the electrolyte green rolls.
[0050] (2) The electrolyte green sheet obtained in step (1) is punched into a 100*100 mm square, and the green sheet is sandwiched with a paper with a roughness of 3 μm, and subjected to a nylon film vacuum heat sealing treatment, and then placed in an isostatic press, and maintained at 70°C and 100 MPa for 30 min. After the pressure maintenance is completed, it is cooled to room temperature, taken out and unpacked, and baked at 50°C for 30 min. The treated electrolyte green sheet is stacked in 6 layers, placed on an alumina porous plate with a porosity of 30% (the weight is less than 200 g, otherwise it will affect the shrinkage of the product and cause cracking), and then covered with a plate of the same type, and the temperature is increased to 550°C at a rate of 1°C / min, and the temperature is kept for 1 h, and then the temperature is increased to 1250°C at a rate of 2°C / min, and the temperature is kept for 6 h, and then the temperature is decreased to 800°C at a rate of 2°C, and the temperature is naturally cooled to room temperature, and the sintering is completed, and the electrolyte sheet is obtained by washing and drying. The roughness of the two sides of the electrolyte sheet was measured to be 2.3μm and 2.3μm respectively, and the thickness was 130μm.
[0051] (3) The cathode and anode powders are LSC and NiO, respectively, with D50 = 0.8 μm. For the cathode active layer, the LSC-YSZ powder is mixed evenly in a ratio of 1:1, pine alcohol and ethyl cellulose are added, and the mixture is dispersed by ball milling with a planetary ball mill. After dispersion, a three-roll mill is used for multiple rolls. The fineness of the slurry is detected by a fineness scraper and is about 3 μm. The slurry configuration is completed and printed by a screen printer. Similarly, the cathode current collector layer is printed: the LSC layer. The anode active layer: the NiO-YSZ powder is mixed evenly in a ratio of 1:1, and the printing is completed as above. The anode current collector layer is a NiO layer, and the principle is the same as above. It should be noted that after each single layer is printed, it is dried and the thickness is measured before printing the next layer. After printing, it is dried at 110°C to obtain a single cell.
[0052] (4) Place the monolithic cell obtained in step (3) on the electrolyte sheet, and then cover it with the electrolyte sheet for sandwiching. The electrolyte can be reused. Heat the temperature to 500°C at a rate of 1°C / min in a debinding and sintering integrated furnace, keep it warm for 1 hour, then heat it to 1050°C at a rate of 0.5°C / min, keep it warm for 5 hours, and then cool it to 600°C at a rate of 2°C / min. End the program and cool it naturally to room temperature to obtain an electrolyte-supported solid oxide fuel cell.
[0053] The electrochemical performance results of the electrolyte sheet obtained in this example, the single-sheet single-cell performance test and the obtained fuel cell tested at 850° C. are shown in Table 2 below.
[0054] Table 2
[0055]
[0056] Example 3
[0057] A method for preparing an electrolyte-supported solid oxide fuel cell comprises the following steps:
[0058] (1) Prepare a certain amount of SSZ powder with a D50 of 0.2 μm, add an organic solvent (a mixed solvent of toluene, ethanol, and isopropanol in a volume ratio of 1:1:1) into a ball mill, and the amount of organic solvent added is 60% of the mass of the SSZ powder. Then, add 2% of the mass of the SSZ powder as a PVA dispersant and stir to dissolve. Then add the prepared SSZ powder and ball mill it on a ball mill for 30 minutes. Then, add 10% of the mass of the SSZ powder as PEG and 15% of the mass of the PVB and ball mill it for 6 hours. Transfer the material to a sand mill and continue to disperse it for 30 minutes. After filtering, transfer it to a degassing tank. Defoaming treatment was carried out under negative pressure of -100 KPa, and stirring was continued. After 30 minutes, a 200-mesh stainless steel filter was installed and connected to the feeding port of the casting machine. The viscosity of the slurry was measured to be 1250 mPa.s after sampling. The maximum temperature of the drying tunnel was adjusted to 70°C, and the knife height was controlled to control the casting thickness to 180 μm. The casting was completed and divided into green rolls to obtain the electrolyte green rolls.
[0059] (2) The electrolyte green sheet obtained in step (1) is punched into a 100*100 mm square, and the green sheet is sandwiched with a paper with a roughness of 3 μm, and subjected to a nylon film vacuum heat sealing treatment, and then placed in an isostatic press, and maintained at 50°C and 120 MPa for 40 minutes, and then cooled to room temperature after the pressure maintenance is completed, taken out and unpacked, and baked at 50°C for 30 minutes. The treated electrolyte green sheet is stacked in 7 layers, placed on an alumina porous plate with a porosity of 40% (the weight is less than 200g, otherwise it will affect the shrinkage of the product and cause cracking), and then covered with a plate of the same type, and the temperature is increased to 350°C at a rate of 2°C / min, and kept warm for 5 hours, and then the temperature is increased to 1480°C at a rate of 3°C / min, and kept warm for 3 hours, and then the temperature is decreased to 800°C at a rate of 2°C, and naturally cooled to room temperature, and sintering is completed, and the electrolyte sheet is obtained by washing and drying. The roughness of the two sides of the electrolyte sheet was measured to be 2.4μm and 2.3μm respectively, and the thickness was 125μm.
[0060] (3) LSCF and NiO are selected as cathode and anode powders respectively, D50 = 0.8 μm, cathode active layer: LSCF-SSZ powder is mixed evenly in a ratio of 1:1, pine alcohol and ethyl cellulose are added, and the powder is dispersed by ball milling with a planetary ball mill. After dispersion, a three-roll mill is used for multiple rolling. The fineness of the slurry is detected by a fineness scraper and is about 3 μm. The slurry is configured and printed using a screen printer; similarly, the cathode current collector layer: LSCF layer printing is completed. Anode active layer: NiO-SSZ powder is mixed evenly in a ratio of 1:1, and the printing is completed as above; the anode current collector layer is a NiO layer, and the principle is the same as above. Note that after each single layer is printed, it is dried and the thickness is measured before printing the next layer. After printing, it is dried at 110°C to obtain a single cell.
[0061] (4) Place the monolithic single cell obtained in step (3) on the electrolyte sheet, and then cover it with the electrolyte sheet for sandwiching. The electrolyte can be reused. Heat it to 200°C at a rate of 0.2°C / min in a debinding and sintering integrated furnace, keep it warm for 4 hours, then heat it to 1300°C at a rate of 2°C / min, keep it warm for 2 hours, and then cool it to 600°C at a rate of 2°C / min. End the program and cool it naturally to room temperature to obtain an electrolyte-supported solid oxide fuel cell.
[0062] The electrochemical performance results of the electrolyte sheet, the single-cell performance test and the fuel cell obtained in this example at 850° C. are shown in Table 3 below.
[0063] Table 3
[0064] Electrolyte sheet relative density Electrolyte sheet warping Single cell warping Fuel Cell OCV Fuel cell power density 98.5% 180μm 220μm 1.25V <![CDATA[395mW / cm 2 ]]>
[0065] Comparative Example 1
[0066] In the preparation method of an electrolyte-supported solid oxide fuel cell of this comparative example, compared with Example 1, in the medium static pressure treatment process in step (2), paper with a roughness of 3 μm is not used to sandwich the electrolyte green body, and the rest is the same.
[0067] In this comparative example, the roughness of the two sides of the electrolyte sheet was measured to be 0.2 μm and 0.25 μm respectively.
[0068] The electrochemical performance results of the electrolyte sheet, the single-cell performance test and the fuel cell obtained in this comparative example at 850°C are shown in Table 4 below.
[0069] Table 4
[0070] Electrolyte sheet relative density Electrolyte sheet warping Single cell warping Fuel Cell OCV Fuel cell power density 98.4 190μm 230μm 1.22V <![CDATA[366mW / cm 2 ]]>
[0071] From the results, it can be seen that if the ceramic green body is not sandwiched with materials of a certain roughness and a certain roughness is not created on the surface of the electrolyte sheet, the surface area of the battery sheet will be reduced, that is, the three-phase interface area in the battery working process will be reduced, resulting in a more obvious decline in the electrochemical performance of the battery.
[0072] Comparative Example 2
[0073] The preparation method of an electrolyte-supported solid oxide fuel cell in this comparative example is compared with Example 1, in which the electrolyte green body is sandwiched by using paper with a roughness of 7 μm in the medium static pressure treatment process in step (2), and the rest is the same.
[0074] As a result, the strength of the electrolyte sheets decreased severely, and most of them broke during the experiment, leading to the failure of the experiment.
[0075] Comparative Example 3
[0076] The preparation method of an electrolyte-supported solid oxide fuel cell in this comparative example is the same as that in Example 1, in step (4), no electrolyte sheet is used for sandwiching during the sintering of the single-cell single cell, and the rest is the same.
[0077] The electrochemical performance results of the electrolyte sheet, the single-cell performance test and the fuel cell obtained in this comparative example at 850°C are shown in Table 5 below.
[0078] Table 5
[0079] Electrolyte sheet relative density Electrolyte sheet warping Single cell warping Fuel Cell OCV Fuel cell power density 98.4 160μm 500μm 1.23V <![CDATA[376mW / cm 2 ]]>
[0080] From the results, it can be seen that the sintering of a single cell does not use electrolyte sheet protection and pressure, which leads to large deformation and warping of the cell due to the different shrinkage rates of the electrodes on both sides during the high-temperature sintering process. At the same time, the electrodes react with the support plate at high temperature and introduce impurities, resulting in a decrease in the electrochemical performance of the battery.
[0081] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an electrolyte-supported solid oxide fuel cell, characterized in that: The method comprises the following preparation steps: (1) mixing the oxide ceramic powder with an organic solvent, a dispersant, a plasticizer, and a binder, dispersing the mixture by ball milling, removing bubbles in vacuum, filtering the mixture, and then forming a film by tape casting to obtain an electrolyte green body; (2) isostatically pressing the electrolyte green body obtained in step (1), drying it, stacking it, debinding and sintering it, washing it, and drying it to obtain an electrolyte sheet; (3) printing the cathode slurry and the anode slurry on both sides of the electrolyte sheet obtained in step (2) by screen printing, and drying to obtain a single-chip single cell; (4) The single cell obtained in step (3) is sandwiched with an electrolyte sheet, and then debinding and sintering are performed to obtain an electrolyte-supported solid oxide fuel cell.
2. The method for preparing an electrolyte-supported solid oxide fuel cell according to claim 1, characterized in that: The oxide ceramic powder in step (1) is YSZ or SSZ ceramic powder with a particle size of 0.1 to 1.5 μm.
3. The method for preparing an electrolyte-supported solid oxide fuel cell according to claim 1, characterized in that: The organic solvent is one or more of toluene, ethanol, isopropanol, and acetone, and the amount of the organic solvent is 30% to 70% of the mass of the oxide ceramic powder; the dispersant is PVA or PAA, and the amount of the dispersant is 0.5% to 3% of the mass of the oxide ceramic powder; the plasticizer is at least one of PEG, DOP, and DBP, and the amount of the plasticizer added is 5% to 10% of the mass of the oxide ceramic powder; the binder is at least one of MC and PVB, and the amount of the binder added is 5% to 15% of the mass of the oxide ceramic powder.
4. The method for preparing an electrolyte-supported solid oxide fuel cell according to claim 1, characterized in that: The filtration in step (1) refers to filtration using a fiber filter element or a stainless steel filter screen with a mesh size of 100 to 500; the thickness of the cast film is controlled between 120 and 200 μm, and the temperature is 30 to 80° C.
5. The method for preparing an electrolyte-supported solid oxide fuel cell according to claim 1, characterized in that: The isostatic pressing process in step (2) covers both sides of the electrolyte green body with rough materials, creates certain rough textures on the surface of the green body, and controls the roughness to be between 1 and 3 μm.
6. The method for preparing an electrolyte-supported solid oxide fuel cell according to claim 1, characterized in that: The isostatic pressing treatment in step (2) has a pressure of 30-150 MPa, a temperature of 30-85° C., and a time of 20-150 min; the drying refers to low-temperature drying at a temperature of 40-70° C. for 2-5 h.
7. The method for preparing an electrolyte-supported solid oxide fuel cell according to claim 1, characterized in that: The number of stacked layers in step (2) is 3 to 10 layers, and the stacked electrolyte green body is pressed up and down with an alumina porous plate having a weight of less than 200g and a porosity of 20% to 40%; the debinding section of the debinding sintering has a heating rate of 0.5 to 2°C / min, a temperature of 250 to 550°C, and is kept warm for 2 to 5 hours; the sintering section has a heating rate of 1 to 3°C / min, a temperature of 1250 to 1480°C, and is kept warm for 3 to 6 hours; and then the temperature is reduced to 800°C at a cooling rate of 1 to 3°C / min, and then the temperature is naturally reduced to room temperature.
8. The method for preparing an electrolyte-supported solid oxide fuel cell according to claim 1, characterized in that: The cathode slurry in step (3) includes cathode current collecting layer powder slurry and cathode active layer powder slurry; the cathode current collecting layer powder slurry is LSM, LSC or LSCF powder slurry with a powder particle size of 0.2 to 1.5 μm; the cathode active layer powder slurry is a mixed slurry of cathode current collecting layer powder and electrolyte oxide ceramic powder in a mass ratio of 1:1 to 1:3; the anode slurry includes anode current collecting layer powder slurry and anode active layer powder slurry; the anode current collecting layer powder slurry is NiO powder slurry with a powder particle size of 0.2 to 1.5 μm; the anode active layer powder slurry is a mixed slurry of anode current collecting layer powder and electrolyte oxide ceramic powder in a mass ratio of 1:1 to 1:3; the screen printing makes the thickness of the cathode current collecting layer 5 to 40 μm, the thickness of the cathode active layer 5 to 20 μm, and the thickness of the anode current collecting layer and the anode active layer 5 to 30 μm; the drying temperature is 90 to 130°C.
9. The method for preparing an electrolyte-supported solid oxide fuel cell according to claim 1, characterized in that: In step (4), the debinding section of the debinding sintering is heated at a rate of 0.2 to 1.5°C / min, the temperature is 200 to 500°C, and the temperature is kept at this temperature for 1 to 4 hours; the sintering section is heated at a rate of 0.5 to 2°C / min, the temperature is 1050 to 1300°C, and the temperature is kept at this temperature for 2 to 5 hours; the temperature is then reduced to 600°C at a rate of 1 to 3°C / min, and then naturally cooled to room temperature.
10. An electrolyte-supported solid oxide fuel cell, characterized in that: It is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for co-sintering cathode and anode of electrolyte-supported solid oxide fuel cell
CN102180669A
Cited By
Interface optimization method of solid oxide fuel cell and cell
CN121416562A